Vaksinasi Sebagai Penanggulangan Pandemi Covid-19 Perspektif Fiqh Islam - Ahmad Fuadi; Tentiyo Suharto (El-Ghiroh : Jurnal Studi Keislaman, 2021)
Indonesia is currently busy with various efforts in the prevention, treatment, and handling of the Covid-19 virus, one of the efforts made by the government is the covid-19 vaccination, the administration of this vaccine has reaped various responses, starting from receiving it totally, rejecting it. totally and accepting conditionally, the groups that refuse to be vaccinated have various backgrounds, ranging from reasons of health concerns to reasons of religion. This research is an analytic descriptive study using a normative juridical approach. The collected data were analyzed qualitatively with deductive and inductive thinking methods. In the end it can be concluded that the problem of Covid-19 vaccination, which is suspected to contain unclean elements, does not need to be questioned, as long as in medical tests it will not endanger human health or in maqashid language, as long as it reflects hifzh an-nafs or maintains the soul and hfzh an-nasl or maintain humans as a whole.